Total Antioxidant Status and Lipid Peroxides in Patients with Pulmonary Tuberculosis - Deepak Parchwani; S. P. Singh; Digisha Patel (Medsci Publications, 2011)
Free radicals are potentially damaging to tissues, producing irreversible damage to biomolecules such as enzymes, proteins and membrane lipids. The current study was conducted to assess the concentration of malionaldehyde(MDA) as a marker of lipid peroxidation and total antioxidant status(TAS) in patients with active pulmonary tuberculosis and to examine the influence of chemotherapy on these parameters. 45 patients were enrolled into the study. 20(Group I) had only small radiographical changes and were sputum negative. The remainder 25(Group II) had advanced pulmonary tuberculosis and were sputum smear positive. The control group consisted of 20 clinically healthy individuals. In group I & II blood samples were collected for examination before and after 6 months of treatment period with tuberculostatic drugs. Data was analyzed by SPSS software. In patients with pulmonary tuberculosis, both before and after chemotherapy, serum MDA concentration was significantly higher and the content of TAS was significantly lowered in comparison to the control group, though in the course of treatment MDA concentration decreased significantly while the concentration of TAS were stable. These results suggest that increased circulating levels of free radical activity along with decreased TAS are found in active pulmonary tuberculosis and hence may play a role in the resultant fibrosis. It also reinforces the belief that inclusion of antioxidants to the therapy may prove to be useful.